Nanopore Wall-Liquid Interaction under Scope of Molecular Dynamics Study: Review; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Tsukanov A. A. Aleksey Alekseevich (2017, 2017)
Title screen